Sensitivity study for a 4-electrode Focused Impedance Method (FIM) using Finite Element Method analysis (Bangladesh Journal of Medical Physics, 2015)
Focused Impedance Method (FIM) is a recent technique, innovated by one of the authors at Dhaka, and shows a promise in providing practical results with a minimum of instrumentation complexity. Out of three version using 8, 6 and 4 electrodes, this paper concentrates on the 4-electrode FIM. Earlier work mainly used phantom experiments to verify the concept and analytical methods for a semi-infinite medium. The present work uses Finite Element Method (FEM), implemented by a software package named COMSOL to obtain various sensitivity graphs for 4-FIM. Firstly, it has verified the focusing effect for a homogenous medium using point sensitivity calculations. Secondly, it obtained simulated impedances for finite sized objects embedded in a medium of uniform conductivity considering five important variables namely, electrode spacing, object size, object resistivity, background resistivity and depth. In this paper the effect of each of these variables has been studied by keeping the other four constant. The obtained graphs give an insight which is expected to lead to quantitative assessment of target objects, needed in physiological study and diagnosis.Bangladesh Journal of Medical Physics Vol.7 No.1 2014 1-7